Pengaruh Likuiditas, Profitabilitas dan Leverage terhadap Nilai Perusahaan pada PT. Bank Muamalat Tahun 2016-2023 - Intan Rahma Lucretia Koto; Ujang S.Mubarok; Zulfia Rahmawati (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study looks at how liquidity, profitability, and leverage laffect the value of a company, specifically PT Bank Muamalat Indonesia, between the years 2016 and 2023. It uses a quantitative and method and gets its data from published annual financial reports. All the financial reports from that time are considered the full set of data, but only 32 reports were chosen as a sample. These reports were picked based on specific criteria that match the variables being studied.The factors that are looked at are lliquidity, measuredl by the lCurrent Ratio (CR), profitabilityl measuredl by Returnl on Assetsl (ROA), and leveragel measured by and Debt tol Equity Ratiol (DER). The company valuel is measuredl byl Price to Book Value (PBV). The data was analyzed using SPSS software with methods like multiplel linear regression, t-test, and F-test.The findings show that liquidityl and leveragel have a strong positive effect on company value, while profitability has a negative effect.lWhen all threel factors are lconsidered together, they have a positive and significantl impact on company value. This suggests that internal factors like liquidity and profitability, and how a company uses debt are important in determining its overall lvalue. this study confirms based on the results obtained that internal company factors, especially liquidity, profitability, and capital structure, are important determinants in determining company value.